2016
DOI: 10.1097/ijg.0000000000000138
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Glaucoma and Its Association With Diabetic Retinopathy in a Diabetic Retinopathy Screening Program

Abstract: The overall prevalence of glaucoma in this diabetic population, based on finding increased cupping of optic disc in a teleretinal screening program was 1.8% (95% confidence interval, 1.0-3.0).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…The prevalence of other eye diseases should be interpreted with caution because this is a screening programme for DR and the quality assurance was ensured for the grades of DR, not other eye diseases. Our previous studies on detection of increased cup-to-disc ratio and detection of AMD in a diabetic screening programme have highlighted the detection of these conditions on a pilot cohort (n=2182) 25 26…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of other eye diseases should be interpreted with caution because this is a screening programme for DR and the quality assurance was ensured for the grades of DR, not other eye diseases. Our previous studies on detection of increased cup-to-disc ratio and detection of AMD in a diabetic screening programme have highlighted the detection of these conditions on a pilot cohort (n=2182) 25 26…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have seen good intra- and interobserver agreement among ophthalmologists, optometrists, and even nonmedical qualifiers [ 26 28 ]. In our case, we have models similar to other detection programs that evaluate the retina and also the optic disc, such as in Hong Kong or the UK, where glaucoma specialists [ 24 , 29 ] are not used. More research is needed in this area, for example, establishing staggered screening between subspecialties.…”
Section: Discussionmentioning
confidence: 99%
“…Other countries have various local or specific population screening programs, such as the DR screening program of the Veterans Health Administration in the United States (24). Concurrent optic disc evaluation in DR screening programs can be useful in diagnosing incident cases of glaucoma, which might otherwise go undetected (13-16). We found that 91 patients from a total of 3,697 (2.46%) had optic disc features suspicious for glaucoma on photographic DR screening, with 49 (77.78%) of the 63 who attended glaucoma review confirmed as glaucoma or glaucoma suspects and remaining under the care of the glaucoma specialist clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, by way of internal control, they also clinically assessed 175 randomly selected patients who were not considered to have suspicious discs by the DR graders, and only 4% of these patients had suspicious discs. In 2014, ­Gangwani et al (16) found that 81 diabetic Chinese subjects from a total of 2,182 screened (3.7%) had suspicious optic discs requiring referral to the glaucoma clinic. They diagnosed 40 of the 73 patients who presented with glaucoma (55%) and they did not subclassify patients into a category of glaucoma suspect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation